Use of Low-Dose Recombinant Factor Ⅶa for Uncontrolled Perioperative Bleeding - Zhi-gang Chang MD, PhD; Xin Chu MD; Wen Chen MD; Jun-hua Hu MD; Ji-wu Gong MD; Da-dong Liu MD; Qing He MD; Zhe Feng MD; Shi-rou Xiao MD; Ya-lin Liu MD (SAGE Publishing, 2020)
Background: Recombinant activated factor VIIa (rFVIIa) is a prohemostatic agent initially approved for use in hemophilia patients and has also been used for a diverse range of off-label indications in the context of massive uncontrolled blood loss; however, no convincing evidence exists regarding the optimal dose of rFVIIa to treat uncontrolled bleeding in surgical patients. Aim: To evaluate the effects and safety of a very low dose of rFⅦa in patients with uncontrolled perioperative bleeding in the surgical intensive care unit (ICU). Methods: 55 patients from Beijing Hospital, who received rFⅦa between July 2004 and November 2018 for uncontrolled perioperative bleeding were included. The controls were matched for age, sex, severity, and operation type. The baseline demographics, survival, changes in bleeding and transfusion, coagulation parameters and complications were analyzed. Results: A low dose of rFⅦa (2.0∼3.6 mg, with a median dose of 39.02 μg/kg) appears to be effective in controlling massive hemorrhage (with an effective rate of 74.55%), and can reduce volume of red blood cell transfusion, improve coagulation status, while has a relatively low risk of thromboembolic complications (3.6%). Conclusion: In patients with uncontrolled perioperative bleeding, a low dose of rFⅦa could be used when traditional methods are ineffective.